The development of lamb production systems using one type of Sudanese sheep - Pollott, G.E. (1979)
The study compares the growth performance of Watish lambs in the Sudan under traditional production systems with those of lambs kept in feedlots and on irrigated pastures by a series of trials designed to investigate the components of more intensive systems of lamb production. It investigates some attributes of lamb carcasses in light of local market conditions and studies why lambs kept under the traditional system are sold at over two years of age while more intensively reared lambs can be sold at 8 to 14 months of age depending on the system.